Pengaruh Disiplin Kerja dan Fasilitas Kerja terhadap Produktivitas Kerja Karyawan Ibis Hotel Padang - Arif Budiman; Nidia Wulansari (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
The research aims to analyze how far work discipline and work facilities influence the level of effectiveness of employee performance at Ibis Hotel Padang. The method applied in this research is a descriptive method with a quantitative approach. Data in the form of numbers was obtained through distributing questionnaires, and processed using SPSS version 26. The research results showed that work discipline and work facilities had an impact on employee effectiveness. Hypothesis testing using analysis with multiple linear regression results shows that the F value of 39.272 is greater than the F value of 3.15, with a significance level of 0.00 which is smaller than 0.05. This shows that the variables work discipline (X1) and work facilities (X2) have an effect on work productivity (Y), and the alternative hypothesis (H1) is accepted. Furthermore, the regression coefficient for variable X1 was obtained at 0.088 with a significance level of 0.019 (smaller than 0.05). Meanwhile, variable X2 has a regression coefficient of 0.654 with a significance level of 0.00 (smaller than 0.05). This indicates that an increase of one in work discipline may increase the effectiveness of employee performance by 0.088, while every increase of one in work facilities will increase the effectiveness of employee performance by 0.654. Multiple linear regression analysis shows that the influence of work discipline (X1) and work facilities (X2) on employee performance effectiveness (Y) is 55.7%.